Thrombotic thrombocytopenic purpura during pregnancy versus imitator of preeclampsia. Issue 10 (10th August 2015) - Gasparri, Maria Luisa; Bellati, Filippo; Brunelli, Roberto; Perrone, Giuseppina; Pecorini, Francesco; Papadia, Andrea; Meloni, Giovanna; Trisolini, Silvia Maria; Gozzer, Maria; Domenici, Lavinia; Lecce, Francesca; Benedetti Panici, Pierluigi
<x xml:space="preserve">Abstract</x> BACKGROUND Thrombotic thrombocytopenic purpura (TTP) is a severe disorder affecting the microcirculation of multiple organs due to a systemic endothelial cell injury secondary to a deficiency in ADAMTS13 (a disintegrin and metalloprotease with thrombospondin type 1 motif, member 13) activity. TTP is a rare complication of pregnancy with a poor prognosis and high fetal mortality, especially when it occurs during the first trimester. Recent data have supported that effective treatment of TTP is plasma therapy. Unfortunately a major problem remains in the delay in diagnosis due to confounding factors between other "imitators of preeclampsia." Rapid and readily available laboratory testing to quickly diagnose TTP is desperately needed to improve care and to save mother and future child life. CASE REPORT We describe a rare case of successful pregnancy after TTP manifestations occurring in the first trimester; most importantly, our experience represents the first case of atypical manifestation due to neurologic and kidney manifestations preceding laboratory assay alterations. RESULTS We treated a patient with plasma replacement of 30 mL/kg/day and daily plasmapheresis in combination with continuous infusion of fresh‐frozen plasma 10 mL/kg/day. The response of clinical manifestation immediately improved. At 30 weeks, the patient had multiple episodes of high blood pressure and concomitant decrease of hemoglobin and platelet count, so a cesarean section was immediately performed. She delivered a healthy female baby. CONCLUSION Early diagnosis by ADAMTS13 activity, occasionally occurring before clinical manifestations, aided us in promptly administering commended and life‐saving treatments.